2008
DOI: 10.1016/j.drugpo.2007.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, cannabis, and methamphetamine use and other risk behaviours among Black and Coloured South African women: A small randomized trial in the Western Cape

Abstract: Background-There is a pressing need for brief behavioural interventions to address the intersection of high HIV prevalence, increasing substance use, and high-risk sex practices among South African women. The primary aim of this pilot, randomized trial was to examine whether an adapted evidence-based intervention would be equally, more, or less effective at reducing HIV risk behaviours when delivered using an individual or group format. The secondary aim was to examine differences between Black and Coloured So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 39 publications
6
74
1
Order By: Relevance
“…What literature there is addresses the dental, psychiatric and social impact of drug use in SA, particularly in the Western Cape. [14][15][16] This study reviewed patients attending a single tertiary hospital with hypertension and/or chronic kidney disease (CKD) and who reported the use of methamphetamines.…”
mentioning
confidence: 99%
“…What literature there is addresses the dental, psychiatric and social impact of drug use in SA, particularly in the Western Cape. [14][15][16] This study reviewed patients attending a single tertiary hospital with hypertension and/or chronic kidney disease (CKD) and who reported the use of methamphetamines.…”
mentioning
confidence: 99%
“…7,8 The analysis of the findings from the eight studies conducted in Cape Town, however, found less consistent findings of an association between MA use and having sex without a condom, with several studies indicating an association 10,11,12,15 and others not. 3,10,15 The one study which found that MA use was more associated with condom use 11 , also found that MA users were less likely to have sex under the influence of alcohol or other drugs in contrast to three studies that found the opposite. 3,13,15 In the former study, 45 of the 47 MA users were Coloured and only two were Black African, whereas only 7 of the non-MA users were Coloured and 55 were Black African.…”
Section: Discussionmentioning
confidence: 96%
“…In a pilot intervention study of 113 Black African and Coloured drug using women from four townships in Cape Town undertaken in 2005 11 , poor, females who had used MA in the past 30 days (43.1%) were significantly less likely than poor females who had used other drugs to have had sex under the influence of alcohol or other drugs in the past 30 days (10 . Some of the data presented above were not included in the published paper but from additional information available to two of the authors who were also authors on this paper (WW,CP)…”
Section: Studymentioning
confidence: 99%
“…For Black women, more alcohol consumption was linked to more frequent sex, although they often reported having only one partner. On the other hand, Coloured women were more likely to have multiple partners (1.53 partners in the past 30 days for Coloured women, vs. 0.98 for Black women) (Wechsberg et al, 2008). Hargreaves et al (2002) found an interesting link between alcohol use, age, socio-economic status and HIV prevalence.…”
Section: Heterosexual Couples Outside Of the United Statesmentioning
confidence: 99%
“…In a sample of 112 women [60 Black and 52 Coloured (mixed race) persons], ethnic differences in terms of drinking patterns were observed, despite both groups reporting that they had sex while under the influence of alcohol (Wechsberg et al, 2008). For Black women, more alcohol consumption was linked to more frequent sex, although they often reported having only one partner.…”
Section: Heterosexual Couples Outside Of the United Statesmentioning
confidence: 99%